Framing English Education Policy in Indonesia: A Comparative Critical Discourse Analysis of Media Representation in The Jakarta Post - Ai Aas Astriyani; Didin Nuruddin Hidayat; Nida Husna (Universitas Islam Negeri Palopo, 2025)
This study examines how English education policy in Indonesia is ideologically framed in news media by comparing two Jakarta Post articles from 2013 and 2025. While most Critical Discourse Analysis (CDA) research in Indonesia has focused on textbooks and classroom practices, little attention has been paid to how media constructs English policy over time. The qualitative CDA analysis followed three stages: textual coding of lexical choices and modality, framing analysis using Entman’s problem–cause–evaluation–solution matrix, and cross-period comparison of the 2013 and 2025 articles. The findings show a marked shift: the 2013 article frames English as an optional local initiative, while the 2025 article presents it as a compulsory national priority linked to teacher professionalism and global competitiveness. The study concludes that The Jakarta Post not only reports policy changes but also shapes public ideology by reinforcing neoliberal and globalizing discourses in English education. These findings have important implications for policymakers, curriculum developers, and teachers seeking to understand how media discourse normalizes accountability and global competitiveness in education reform.